2010
DOI: 10.1007/978-3-642-16373-9_23
|View full text |Cite
|
Sign up to set email alerts
|

Full Satisfiability of UML Class Diagrams

Abstract: Abstract. UML class diagrams (UCDs) are the de-facto standard formalism for the analysis and design of information systems. By adopting formal language techniques to capture constraints expressed by UCDs one can exploit automated reasoning tools to detect relevant properties, such as schema and class satisfiability and subsumption between classes. Among the reasoning tasks of interest, the basic one is detecting full satisfiability of a diagram, i.e., whether there exists an instantiation of the diagram where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The above results have been refined and extended to full satisfiability of UCDs by Artale et al [2] and Kaneiwa et al [30]; upper (resp., lower) bounds are obtained by a reduction to (resp., from) satisfiability of UCDs. In [2], classes of UCDs were identified for which statisfiability is np-complete and nlogspacecomplete by restricting the constructs allowed in the diagrams. In [30], it has also been shown that there exists a fragment of UCDs for which full satisfiability is in ptime.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The above results have been refined and extended to full satisfiability of UCDs by Artale et al [2] and Kaneiwa et al [30]; upper (resp., lower) bounds are obtained by a reduction to (resp., from) satisfiability of UCDs. In [2], classes of UCDs were identified for which statisfiability is np-complete and nlogspacecomplete by restricting the constructs allowed in the diagrams. In [30], it has also been shown that there exists a fragment of UCDs for which full satisfiability is in ptime.…”
Section: Introductionmentioning
confidence: 91%
“…The exptime membership is obtained by providing a polynomial translation of UCD constructs to DLR if d KBs [16]. The above results have been refined and extended to full satisfiability of UCDs by Artale et al [2] and Kaneiwa et al [30]; upper (resp., lower) bounds are obtained by a reduction to (resp., from) satisfiability of UCDs. In [2], classes of UCDs were identified for which statisfiability is np-complete and nlogspacecomplete by restricting the constructs allowed in the diagrams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistency of class diagrams is studied in Kaneiwa and Satoh [2010] and Artale et al [2010]. Kaneiwa and Satoh [2010] provide upper bounds by introducing optimized algorithms for deciding class diagram consistency for various combinations of constraints.…”
Section: Consistencymentioning
confidence: 99%
“…Correctness of a class diagram involves consistency [Andre et al 2000;Berardi et al 2005;Queralt and Teniente 2008;Artale et al 2010;Kaneiwa and Satoh 2010;Jarrar and Heymans 2008] and finite satisfiability [Lenzerini and Nobili 1990;Thalheim 2000;Calvanese and Lenzerini 1994;Boufares and Bennaceur 2004;Maraee and Balaban 2007;Cabot et al 2008;Berrabah and Boufarès 2008]. …”
Section: Correctness Of Class Diagramsmentioning
confidence: 99%